Carnivores, Colonization, and Conflict: A Qualitative Case Study on the Intersectional Persecution of Predators and People in Namibia. (30th December 2016) - Rust, Niki A.; Taylor, Nik
ABSTRACT: Nonhuman carnivores have historically been demonized, lethally controlled, and extirpated throughout many parts of the world—indeed, they bear the brunt of this in some places still today. To understand why this is still occurring, it is important to appreciate the historical events that have shaped and led to this situation. We use a qualitative case study in Namibia that draws on an archival review and eight months of ethnography to describe the widespread control of nonhuman carnivores in the country, from the 1800s to the present day. Calling upon Val Plumwood's eco-feminist typology of domination of the "Other, " and integrating it with current advances in inter- sectional theory, we explain the apparent parallels in this process of domi- nation of Namibian nonhuman predators alongside its Indigenous peoples by European settlers. We discuss the process of colonization of predators and people, highlighting how perceived power differentials provided an ideal situation to dominate these presumed "Others." We conclude with a number of recommendations that could begin to reconcile conflicts between people and predators, and between different groups of people.